The Genesis of the Zionist Paradigm in Jewish History: Exploring Ben-Zion Dinur's Worldview - Ruzhansky, Vladimir («Քոփի Փրինթ» տպագրատուն)
The 1920s and 30s marked a pivotal period for the genesis of the modern Jewish state and its historical narrative. It was during this era that the Zionist paradigm of Jewish history took shape, serving as the cornerstone of collective memory and the bedrock of national identity for successive generations of Israelis. The initial cohort of Zionist historians astutely grasped the pivotal role of historical scholarship in shaping a national identity, particularly in advancing the Zionist ambition of rejuvenating the Jewish state and cultivating a novel Jewish identity - the Israeli identity. In pursuit of these aspirations, Zionist historians grappled with formidable challenges, chiefly centered around establishing a scholarly foundation validating the unity of the Jewish people and their enduring connection to the land of Israel, known as Eretz Israel. This paper endeavors to delineate the defining traits of Zionist historians during this epoch, drawing upon the prominent figure exemplifying this ethos, Professor Ben-Zion Dinur who endeavored to harmonize ideological allegiance with scholarly veracity. Furthermore, the paper delves into the fundamental elements comprising the Zionist narrative within Jewish history. 1920-30-ական թվականները նշանակալից են եղել ժամանակակից հրեական պետության և վերջինիս ստեղծման համար: Հենց այս դարաշրջանում է ձևավորվել հրեական պատմության սիոնիստական պարադիգմը, որը ծառայել է որպես հավաքական հիշողության հիմնաքար և ազգային ինքնության հիմք իսրայելցիների հաջորդական սերունդների համար: Սիոնիստ պատմաբանների սկզբնական խումբը ըմբռնեց պատմական գիտության առանցքային դերը ազգային ինքնության ձևավորման գործում հատկապես հրեական պետության երիտասարդացման սիոնիստական նկրտումներն առաջ մղելու և նոր հրեական ինքնություն՝ իսրայելական ինքնություն, մշակելու գործում: Այս ձգտումներին հետամուտ լինելով՝ սիոնիստ պատմաբանները բախվեցին ահռելի մարտահրավերների հետ, որոնք հիմնականում կենտրոնացած էին հրեա ժողովրդի միասնության և Իսրայելի երկրի հետ նրանց հարատև կապի հաստատման վրա հիմնված գիտական հիմնադրամի վրա, որը հայտնի է որպես Էրեց Իսրայել: Սույն հոդվածը փորձում է ուրվագծել այս դարաշրջանում սիոնիստ պատմաբանների որոշիչ գծերը՝ հենվելով հրեա նշանավոր գործչի՝ պրոֆեսոր Բեն-Սիոն Դինուրի վրա, ով ջանում էր ներդաշնակեցնել գաղափարական հավատարմությունը գիտական ճշմարտության հետ:
Keywords: Israel; History